Answer:
1.16
Step-by-step explanation:
Given that;
For some positive value of Z, the probability that a standardized normal variable is between 0 and Z is 0.3770.
This implies that:
P(0<Z<z) = 0.3770
P(Z < z)-P(Z < 0) = 0.3770
P(Z < z) = 0.3770 + P(Z < 0)
From the standard normal tables , P(Z < 0) =0.5
P(Z < z) = 0.3770 + 0.5
P(Z < z) = 0.877
SO to determine the value of z for which it is equal to 0.877, we look at the
table of standard normal distribution and locate the probability value of 0.8770. we advance to the left until the first column is reached, we see that the value was 1.1. similarly, we did the same in the upward direction until the top row is reached, the value was 0.06. The intersection of the row and column values gives the area to the two tail of z. (i.e 1.1 + 0.06 =1.16)
therefore, P(Z ≤ 1.16 ) = 0.877
The equation would be 6x+x=63. Not sure how the models play out, but good luck
Given:
There are given that the zeroes and degrees of the polynomial:
![\begin{gathered} \text{zeros:}-2,2,4 \\ \text{Degres:}3 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Ctext%7Bzeros%3A%7D-2%2C2%2C4%20%5C%5C%20%5Ctext%7BDegres%3A%7D3%20%5Cend%7Bgathered%7D)
Explanation:
From the concept of a polynomial:
A polynomial has a as zero if and only if (x -a) is a factor of the polynomial.
Then,
From the given polynomial:
![f(x)=(x+2)(x-2)(x-4)](https://tex.z-dn.net/?f=f%28x%29%3D%28x%2B2%29%28x-2%29%28x-4%29)
Then,
![\begin{gathered} f(x)=(x+2)(x-2)(x-4) \\ f(x)=(x^2-2x+2x-4)(x-4) \\ f(x)=(x^2-4)(x-4) \\ f(x)=x^3-4x^2-4x+16 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20f%28x%29%3D%28x%2B2%29%28x-2%29%28x-4%29%20%5C%5C%20f%28x%29%3D%28x%5E2-2x%2B2x-4%29%28x-4%29%20%5C%5C%20f%28x%29%3D%28x%5E2-4%29%28x-4%29%20%5C%5C%20f%28x%29%3Dx%5E3-4x%5E2-4x%2B16%20%5Cend%7Bgathered%7D)
Final answer:
Hence, the polynomial is shown below:
You have too divide 2 and 7 and 8 divided by the sum and that’s your answer